Task-dependent cross-frequency neural coupling during postural perturbation: insights from EEG-based assessment in elite freestyle aerial skiers - Cheng, Yuqi; Fu, Ao; Guo, Youcai; Gao, Jie; Chen, Yongxia; Qi, Qianrong; Guo, Feng; Wang, Xin (Frontiers in Physiology, 2025)
BackgroundCross-frequency coupling (CFC), particularly phase–amplitude coupling (PAC), reflects hierarchical interactions between neural oscillations and plays a critical role in sensorimotor integration. However, its functional relevance during balance control under sensory perturbations remains insufficiently understood.ObjectiveThis study aimed to investigate PAC characteristics during postural control tasks of varying difficulty in elite freestyle aerial skiers versus non-athlete controls.MethodsEEG signals and center of pressure (COP) data were recorded from participants performing six standing balance tasks on stable and unstable surfaces. Postural control was assessed using center of pressure data, which represent the point location of the body’s vertical ground reaction force vector and are commonly used to quantify sway and balance performance during stance. Mean Vector Length Modulation Index (MVLmi) and PAC analyses were applied to assess oscillatory interactions.ResultsSurface instability significantly modulated PAC strength across frequency bands (P < 0.05). Athletes exhibited task-specific enhancements in alpha-gamma and delta-gamma coupling during single-leg and double-leg stance. These coupling patterns were more spatially localized and showed trends consistent with superior postural control. In contrast, non-athletes showed widespread PAC increases under perturbation, but with less effective balance performance. Hemispheric asymmetries were observed during single-leg stance: athletes demonstrated contralateral dominance during right-leg tasks and ipsilateral coupling shifts during unstable left-leg stance, indicating dynamic lateralized control shaped by training. Across conditions, athletes showed higher PAC strength and lower sample entropy, reflecting more efficient and adaptable cortical strategies for postural regulation.ConclusionPAC strength is closely linked to postural performance and varies with task complexity and surface condition. These findings highlight the role of training-induced neuroplasticity in modulating cortical dynamics for balance control, offering new insights for targeted neuromodulatory interventions and neurofeedback-based training strategies.